2011
DOI: 10.1371/journal.pgen.1002339
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Coordination of Gene Networks by Zelda in the Early Drosophila Embryo

Abstract: In past years, much attention has focused on the gene networks that regulate early developmental processes, but less attention has been paid to how multiple networks and processes are temporally coordinated. Recently the discovery of the transcriptional activator Zelda (Zld), which binds to CAGGTAG and related sequences present in the enhancers of many early-activated genes in Drosophila, hinted at a mechanism for how batteries of genes could be simultaneously activated. Here we use genome-wide binding and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
355
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(394 citation statements)
references
References 61 publications
22
355
2
2
Order By: Relevance
“…In the activated CRMs, this CAGGTA motif is extended by guanidine and cytosine at positions 7 and 8, respectively (Fig. 4A); this extended motif overlaps a reported motif for Zelda, a TF required for the activation of gene expression in the early embryo (ten Bosch et al 2006;Liang et al 2008;Harrison et al 2011;Nien et al 2011).…”
Section: Enhancer Architecture Of Snail-bound Crmsmentioning
confidence: 52%
“…In the activated CRMs, this CAGGTA motif is extended by guanidine and cytosine at positions 7 and 8, respectively (Fig. 4A); this extended motif overlaps a reported motif for Zelda, a TF required for the activation of gene expression in the early embryo (ten Bosch et al 2006;Liang et al 2008;Harrison et al 2011;Nien et al 2011).…”
Section: Enhancer Architecture Of Snail-bound Crmsmentioning
confidence: 52%
“…Vielfaltig is sufficient to activate enhancers that contain TAGteam motifs and required for early gene expression and cellularization (Liang et al 2008). While this work was under revision, it has further been shown that Vielfaltig binds to ;60% of all genomic instances of the TAGteam motif (Harrison et al 2011;Nien et al 2011). Our demonstration that Vielfaltig is a key determinant of early binding is intriguing and suggests that Vielfaltig might help to open (or keep open) chromatin and allow TFs to access their binding sites on DNA thereby defining early enhancers.…”
Section: Vielfaltig's Tagteam Motif Is a Key Regulator Of Early Tf Bimentioning
confidence: 90%
“…The maternal transcription factor Zelda (Zld; zinc finger early Drosophila activator) plays a primary role for the onset of zygotic genome activation in Drosophila embryos (Liang et al 2008;Nien et al 2011). Zld protein is present in nuclei considerably earlier than other key maternal transcription factors such as Bicoid (Bcd) and Dorsal (Dl) proteins and is bound to gene regulatory regions prior to zygotic genome activation (Harrison et al 2011;Nien et al 2011). Zld binding increases DNA accessibility and facilitates the binding of other transcription factors, including Bcd and Dl, to target enhancers (Foo et al 2014;Xu et al 2014 (Foo et al 2014).…”
Section: Pioneer Factors In Zygotic Genome Activationmentioning
confidence: 99%